2019
DOI: 10.1136/bcr-2019-230822
|View full text |Cite
|
Sign up to set email alerts
|

Atypical haemolytic uremic syndrome secondary to acute pancreatitis: a unique presentation

Abstract: Atypical haemolytic uraemic syndrome (aHUS) is a disease of complement dysregulation and can be fatal if not treated in a timely manner. Although normally associated with triggers such as infection or pregnancy, this case demonstrates acute pancreatitis as the triggering event. The patient’s initial presentation of thrombocytopaenia and acute renal failure was first attributed to a systemic inflammatory response syndrome due to pancreatitis, but with detailed history and further laboratory investigation, we we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…HUS or aHUS are rarely reported as a complication in pediatric ALL and unlike our patient, mostly in the context of active disease. Literature review revealed 6 pediatric cases in which aHUS preceded the diagnosis of acute leukemia,2,4,5,8–10 1 case of simultaneous presentation with ALL,1 2 cases where aHUS occurred during ALL induction chemotherapy,3,6 and 2 cases of HUS during maintenance therapy 1,7. One reported patient presented with Shiga toxin producing Escherichia coli O157:H, a hallmark of typical HUS, followed by a diagnosis of ALL 9…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…HUS or aHUS are rarely reported as a complication in pediatric ALL and unlike our patient, mostly in the context of active disease. Literature review revealed 6 pediatric cases in which aHUS preceded the diagnosis of acute leukemia,2,4,5,8–10 1 case of simultaneous presentation with ALL,1 2 cases where aHUS occurred during ALL induction chemotherapy,3,6 and 2 cases of HUS during maintenance therapy 1,7. One reported patient presented with Shiga toxin producing Escherichia coli O157:H, a hallmark of typical HUS, followed by a diagnosis of ALL 9…”
Section: Resultsmentioning
confidence: 99%
“…Case reports of aHUS that were considered to be associated with ALL therapy include a fatal case of aHUS in a 4-year-old girl during ALL induction therapy, postulated to have been triggered by l -asparaginase. That patient had also received vincristine and dexamethasone 7. Kanchi and colleagues described a child with ALL who developed recurrent aHUS at 23 and 47 weeks of chemotherapy, thought to be a complication from vincristine 8.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are various reports of autoimmune pancreatitis with autoimmune hemolytic anemia [ 11 ], TTP [ 12 ], HUS [ 13 ], and aHUS [ 6 ] in TMA secondary to pancreatitis, and drug-induced TMA [ 14 ] is also a possibility when drugs potentially causing TMA are used before or during hospitalization. However, TMA, including aHUS, must be assumed when pancreatitis is accompanied by elevated creatinine, hemolytic anemia, and low platelets, and peripheral blood smears or assay of ADAMTS13 levels, for example, should be employed for further differentiation of TMA.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the fact that aHUS is an extremely rare disease, with a prevalence of 4.96 per million total population [ 5 ], cases of aHUS triggered by acute pancreatitis are extremely rare in the literature, having been reported only by Barish et al [ 6 ]. This is a case report of an aHUS that appears to have been triggered by acute pancreatitis.…”
Section: Introductionmentioning
confidence: 99%